2017
DOI: 10.21101/cejph.a4897
|View full text |Cite
|
Sign up to set email alerts
|

Level of Education as a Risk Factor for Extensive Prevalence of Cervical Intervertebral Disc Degenerative Changes and Chronic Neck Pain

Abstract: A moderate level of intervertebral disc degenerative changes (grade II and III) was equally matched among all patients, while the overall results suggest a higher level of education as a risk factor leading to cervical disc degenerative changes, regardless of age differences among respondents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…circRNAs that exhibited significantly lower levels in the degenerative group might have a protective effect on disc degeneration; thus, 15 circRNAs with decreased expression in the heat map were selected. To verify the heat map results, patients with fractures were selected as the control group, and three patients with different degrees of lesions were selected according to the Pfirrmann classification 23 . These samples were then analyzed using real-time (RT) quantitative polymerase chain reaction (qPCR), and the expression level of hsa_circ_0035875 was found to decrease with increasing lesion severity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…circRNAs that exhibited significantly lower levels in the degenerative group might have a protective effect on disc degeneration; thus, 15 circRNAs with decreased expression in the heat map were selected. To verify the heat map results, patients with fractures were selected as the control group, and three patients with different degrees of lesions were selected according to the Pfirrmann classification 23 . These samples were then analyzed using real-time (RT) quantitative polymerase chain reaction (qPCR), and the expression level of hsa_circ_0035875 was found to decrease with increasing lesion severity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Those image-based classification focuses on the imaging characteristics of the intervertebral disc, such as the signal intensity of the nucleus and annulus, the nucleus structure, and the disc height. Markotić et al [ 11 ] applied Pfirrmann grades to evaluate CDD in 112 patients, and the results showed that a higher level of education was a risk factor leading to CDD. Also, Chen et al [ 12 ] used the Miyazaki grades to demonstrate that cigarette smoking could accelerate the process of CDD, leading to more severe neck-shoulder pain.…”
Section: Introductionmentioning
confidence: 99%
“…It was originally developed for the grading of lumbar disk degeneration. Nevertheless, it has become the most commonly used classification system in the literature even for cervical spine degeneration [8][9][10][11] . Other authors were able to demonstrate nearly perfect reliability for the assessment of cervical disk degeneration 12 .…”
Section: Introductionmentioning
confidence: 99%